2005
DOI: 10.1161/01.cir.0000164233.09448.b1
|View full text |Cite
|
Sign up to set email alerts
|

Forced Expression of α-Myosin Heavy Chain in the Rabbit Ventricle Results in Cardioprotection Under Cardiomyopathic Conditions

Abstract: Background-The biochemical differences between the 2 mammalian cardiac myosin heavy chains (MHCs), ␣-MHC and ␤-MHC, are well described, but the physiological consequences of basal isoform expression and isoform shifts in response to altered cardiac load are not clearly understood. Mature human ventricle contains primarily the ␤-MHC isoform. However, the ␣-MHC isoform can be detected in healthy human ventricle and appears to be significantly downregulated in failing hearts. The unique biochemical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 35 publications
7
71
0
Order By: Relevance
“…A similar conclusion has been drawn from studies with transgenic rabbit hearts, in which nearly 40% of endogenous βMHC was replaced by the αMHC isoform [6]. James et al have reported that the transgenic expression of the αMHC isoform in rabbit hearts has no apparent detrimental effects under basal conditions, and that these hearts are protected against tachycardia-induced cardiomyopathy [6].…”
Section: Functional Consequences Of Myosin Isoform Shiftmentioning
confidence: 64%
See 4 more Smart Citations
“…A similar conclusion has been drawn from studies with transgenic rabbit hearts, in which nearly 40% of endogenous βMHC was replaced by the αMHC isoform [6]. James et al have reported that the transgenic expression of the αMHC isoform in rabbit hearts has no apparent detrimental effects under basal conditions, and that these hearts are protected against tachycardia-induced cardiomyopathy [6].…”
Section: Functional Consequences Of Myosin Isoform Shiftmentioning
confidence: 64%
“…In a study utilizing a single cell system, Herron et al demonstrated that cardiac myocytes expressing only 12% of the αMHC isoform produced a 52% greater power output than did those expressing only the βMHC isoform [25,110]. As mentioned above, results obtained from transgenic rabbits, which have an MHC profile very similar to that of man, have indicated that hearts in which βMHC was replaced by 40% of αMHC were at an advantage under stress conditions in maintaining heart function [6]. This study also ruled out the possibility that decreased αMHC during human heart failure could be a compensatory mechanism for preserving the energy efficiency of the heart.…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
See 3 more Smart Citations